Listen up or lose out : how to avoid miscommunication, improve relationships, and get more done faster - Bolton, Robert, 1929-; Bolton, Dorothy Grover (AMACOM, 2018)
Want better results? Talk less and listen more. Listening might seem like the easiest thing in the world to do. But most people retain only a fraction of what they hear, resulting in miscommunications and lost opportunities. When you actively listen, you learn to gather perspectives, bridge differences, and resolve problems. Absorbing what a person is saying, thinking, and feeling sets the stage for dramatically improved relationships and increased professional success. Listen Up or Lose Out pulls this underused tool out from the shadows and highlights its role in effective communications.